Torrefaction and Pelleting of Wheat and Barley Straw for Biofuel and Energy Applications - Agu, Obiora S.; Tabil, Lope G.; Mupondwa, Edmund; Emadi, Bagher (Frontiers in Energy Research, 2021)
Microwave (MW)-assisted torrefaction and pelleting could enhance biomass fuel properties and energy applications. Plastic wastes are considered as a replacement source binder in pellets to minimize their effect on the environment as pollutants. High-density polyethylene (HDPE), an extractable plastic from recycling waste, was investigated as a binder for torrefied wheat and barley straw pellets. Fuel pellet characteristics, such as durability, density, tensile strength, and water absorption, were used to evaluate the pellets produced from a single pelleting test. The results showed that the addition of HDPE as a binder significantly increased the pellet quality in terms of density (686.12–982.93 kg/m3), tensile strength (3.68 and 4.53 MPa) for wheat and barley straw, and reduced ash content of the pellet from 10.34 to 4.59% for barley straw pellet and 10.66 to 3.88% for wheat straw pellets. The higher heating value (HHV) increased with increasing biochar mix and HDPE binder blend. The highest HHV value observed for barley straw was 28.34 MJ/kg, while wheat straw was 29.78 MJ/kg. The study further indicated that MW torrefaction of biomass-biochar mix with HDPE binder reduced the moisture adsorption of wheat and barley straw pellets, which can significantly improve their storage capability in humid locations. The moisture uptake ratio for MW-torrefied barley straw pellets was 0.10–0.25 and wheat straw pellets 0.11–0.25 against a moisture uptake ratio of 1.0 for untreated biomass. MW torrefaction of wheat and barley straw with biochar and HDPE binder addition during pelleting is a promising technique to improve biomass fuel pellet properties.